Eudendrium caraiuru sp. n. (Hydrozoa; Anthoathecata; Eudendriidae) from the southeastern coast of Brazil - Marques, Antonio C.; Oliveira, Otto M.p. (Zootaxa, 2003)
Eudendrium caraiuru sp. n. is described for the southeastern coast of Brazil. The species was reported previously from the area as E. glomeratum, a common species of the Mediterranean Sea. However, morphological, morphometrical and ecological data suggest they are diverging lineages, requiring a new specific name for the Brazilian population.